Improving Students' Understanding of Energy Conservation through Training on Making Electrochemical Storage Devices - Nirwan Syarif; Dedi Rohendi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This paper reports the activities aimed at teachers and high school students in Lubuk Linggau, which went smoothly, interspersed with questions and answers. Demo and presentation, which are program activities, also run smoothly. The theme of community service activities is making a supercapacitor and battery and explaining the material used to make both energy storage devices. In addition, the team also presented basic knowledge about potentiostats and multimeters as test instruments related to electrochemistry. The activity went smoothly, interspersed with questions and answers—the demo and training have run smoothly. The theme of program activities includes the demo and training of preparing supercapacitor - batteries, explaining the materials - tools employed to make the energy storage devices. In addition, the team also presented basic knowledge about supercapacitors, batteries, potentiostats, and other tools related to electrochemistry. The activities of teachers and students at school took place very enthusiastically in receiving direction and counseling from the team. The enthusiasm can be seen in the active discussions between the team and members of these community groups. Group members feel the positive value of the activities carried out by the team. Generally, the team and participant can work out the ideas contained in the patent well. The team recommends some extended programs to propose, such as (a) similar activities should be carried out continuously to increase acknowledgment. (b) collaborating with others, and (c) developing online lab work.